A field sentinel study investigating withering syndrome transmission dynamics in California abalones. (January 2022) - Fuller, Ava M.; VanBlaricom, Glenn R.; Neuman, Melissa J.; Witting, David A.; Friedman, Carolyn S.
Abstract: We examined the risk of withering syndrome (WS) rickettsia-like organism (WS-RLO) infection in sentinel red abalone ( Haliotis rufescens ) deployed in modules at two Southern California field sites, one adjacent to an abalone farm and one adjacent to wild abalones. WS-RLO DNA was detected in seawater near modules at the wild abalone site but not near the farm (WS-RLO DNA was detected in the farm effluent). More WS-RLO DNA was detected in tissue from abalone near the farm relative to those near wild abalones (p < 0.05). However, infection prevalence and intensity based on histology were low and similar between sites (p > 0.05) and were independent of WS-RLO DNA loads in abalone tissue and seawater. More stippled (ST)-RLO than WS-RLO were observed with more ST-RLO infections near wild abalone than near the abalone farm (p < 0.05). We demonstrate the utility of caged sentinel abalone to better understand pathogen transmission patterns in the field. Highlights: Sentinel studies effective for monitoring abalone disease dynamics in nature. Quantifying pathogens in the marine environment requires multifaceted approach. Novel stippled form of the pathogen observed in sentinel abalones. Understanding disease transmission can inform abalone recovery.